2007
DOI: 10.1063/1.2774875
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Type, Redshift, and Phase of a Supernova Spectrum

Abstract: Abstract. We present an algorithm to identify the types of supernova spectra, and determine their redshift and phase. This algorithm, based on the correlation techniques of Tonry & Davis, is implemented in the SuperNova IDentification code (SNID). It is used by members of the ESSENCE project to determine whether a noisy spectrum of a high-redshift supernova is indeed of type Ia, as opposed to, e.g., type Ib/c. Furthermore, by comparing the correlation redshifts obtained using SNID with those determined from na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…ling et al 2020), which is consistent with what was found for higher resolution spectra by Blondin & Tonry (2007). As such, we conclude that the performance of SNIascore is consistent with what can be done with SNID when each result and spectrum is manually inspected.…”
Section: Redshiftssupporting
confidence: 91%
See 2 more Smart Citations
“…ling et al 2020), which is consistent with what was found for higher resolution spectra by Blondin & Tonry (2007). As such, we conclude that the performance of SNIascore is consistent with what can be done with SNID when each result and spectrum is manually inspected.…”
Section: Redshiftssupporting
confidence: 91%
“…In order to evaluate the classification performance of SNIascore we have performed comparisons to SNID (Blondin & Tonry 2007) and DASH (Muthukrishna et al 2019b) (Section 5.1). We also evaluate the accuracy of the associated redshift predictions for the SNe Ia that are identified by SNIascore by comparison to host galaxy redshifts and redshifts determined after manual inspection with SNID (Section 5.2).…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum, discussed in Sect. 7, was obtained soon after the discovery with the Las Campanas 2.5-m du Pont telescope (+WFCCD), and crosscorrelated with a library of SN spectra using the "Supernova Identification" code (SNID; Blondin & Tonry 2007). SN 2013gc appeared as a type IIn SN similar to SN 1996L (Benetti et al 1999) at about two months after the explosion.…”
Section: Introductionmentioning
confidence: 99%
“…One is to set it as the midpoint between the last nondetection date (MJD nondet ) and the discovery date (MJD disc ), along with the representative uncertainty determined by (MJD disc − MJD nondet )/2. Another is to perform a comparison between the observed spectra at early times and SNID templates (Blondin & Tonry 2011) to find a best-fit spectral phase. Applying these two methods to their SN II sample, Gutiérrez et al (2017) find a mean offset of 0.5 d between them.…”
Section: Photometric Evolutionmentioning
confidence: 99%